Studying the Corrosion Effect of Fixed Orthodontic Appliances on Thyroid Hormones - Al-Zubaidi, Hind.T.H.; Al-Issa, Yasser A.H. (Iraqi Journal of Science, 2023)
This study aimed to determine the nickel (Ni), and chromium (Cr) ions amounts and investigate their potential effects on thyroid hormones in patients’ saliva who were receiving treatment with fixed orthodontic appliances (FOA). In this study, 42 FOA volunteers participated, and all samples were obtained from a specialized center for manufacturing and orthodontics in Bab Al-Moadham, Baghdad, Iraq. According to the findings, individuals with fixed orthodontics have significantly higher levels of the thyroid hormones (P<0.05) FT3 and FT4 than those who did not have orthodontic treatment, whereas there were no significant changes in TSH (P=0.599). Additionally, the amounts of Ni+2 and Cr+3 were considerably higher in the individuals receiving metallic orthodontic treatment (P <0.0001). The findings of this investigation support the hypothesis that corrosion metals from the FOA have a meaningful impact on the concentration of Ni and Cr ions and, consequently, on the thyroid and salivary functioning of the patient group.